2004
DOI: 10.1029/2004gb002243
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations of fluxes of NO, NO2, N2O, CO2, and CH4 in a tropical rain forest ecosystem

Abstract: [1] Fluxes of N 2 O, NO, NO 2 , CO 2 , and CH 4 were measured with high temporal resolution for 3 months at a tropical rain forest site in Queensland, Australia, using automated measuring systems. During this period, representing the transition between dry and wet season, huge pulses of NO emissions from the soil exceeding 500 mg N m À2 h À1were observed with the onset of the first rainfalls. . Though a significant amount of the NO emitted from the soil was redeposited to the soil surface after its oxidation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
152
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(181 citation statements)
references
References 25 publications
24
152
0
2
Order By: Relevance
“…Pulses of soil N 2 O emission were observed in the three forests in April 2006 (Fig.3a-c). This result was consistent with previous studies that found re-wetting of soils after prolonged dry periods could stimulate pulses of N 2 O emission (Davidson et al 2000;Butterbach-Bahl et al 2004;Werner et al 2006). Such N 2 O pulse emissions were associated with the rapid microbial consumption of NH þ 4 or NO À 3 accumulated during the dry period (Davidson et al 2000).…”
Section: Soil N Availability Indicessupporting
confidence: 82%
See 1 more Smart Citation
“…Pulses of soil N 2 O emission were observed in the three forests in April 2006 (Fig.3a-c). This result was consistent with previous studies that found re-wetting of soils after prolonged dry periods could stimulate pulses of N 2 O emission (Davidson et al 2000;Butterbach-Bahl et al 2004;Werner et al 2006). Such N 2 O pulse emissions were associated with the rapid microbial consumption of NH þ 4 or NO À 3 accumulated during the dry period (Davidson et al 2000).…”
Section: Soil N Availability Indicessupporting
confidence: 82%
“…The result was consistent with previous studies in tropical forests. Butterbach-Bahl et al (2004) found a linear correlation between soil moisture contents and N 2 O emissions for tropical forest soils in Northern Queensland, Australia. Kiese and Butterbach-Bahl (2002) also reported a linear correlation between N 2 O emissions and soil moisture contents less than 60%, but noted a decline in N 2 O emissions at higher moisture levels, which is most likely due to the increasing formation of N 2 rather than N 2 O.…”
Section: Soil N Availability Indicesmentioning
confidence: 99%
“…In contrast to the general idea that soil moisture content is an important driver for CH 4 fluxes (Butterbach-Bahl et al 2004;Curry 2007;Davidson et al 2004;Keller and Reiners 1994), neither temporal nor spatial variability of net CH 4 exchange could be explained by it. The main reason for this lack of correlation between soil moisture content and net exchange of atmospheric CH 4 is probably the absence of a pronounced dry season and the resulting small variation in soil moisture content.…”
Section: Ch 4 Fluxes and Their Controlsmentioning
confidence: 60%
“…Peculiarly, the high NO flux (up to 214.9 ng N m -2 s -1 , mean 57.5 ng N m -2 s -1 ) was observed from a tropical forest by Butterbach-Bahl et al (51). In this study, our data indicate that the NO emissions decreased with altitude in the entire growth season, whereas those from forest soils are much higher than that from tundra soil and volcanic soil ( Figure 4A), suggesting that field NO emissions are much more dependent on soil nitrogen content and nitrogen input (see Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 91%